ANALISIS PENGARUH KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI - Cahyaningsari, Esti Puji; Yuliati, Yuliati (STIE PENA, 2024)
This study aims to determine the influence of Leadership, Motivation and Work Discipline on Employee Performance. The population in this study is Employees at the Gajahmungkur District Office. Sampling was carried out using the Saturated Sampling method, which was a sample of 68 respondents. The types of data used are primary and secondary data. This study uses a questionnaire in its data collection. The test techniques used are validity tests, reliability tests, classical assumption tests including normality tests, multicollinearity tests, and heterokedasticity tests. The hypothesis test in this study uses a partial test (t test), a simultaneous test (F test), and a determination coefficient test (R Square) using the SPSS version 23 application. The results of this study show that Leadership has no effect on Employee Performance which is obtained by a figure of -1,250< ttable 1.66901 and a significance value of 0.216 > 0.05. Motivation had a positive and significant effect on Employee Performance obtained from 2.209 > table 1.66901 and a significance value of 0.031 < 0.05. Work Discipline had a significant effect on Employee Performance obtained from 4.461 > table 1.66901 and a significance value of 0.001 < 0.05. Leadership, Motivation and Work Discipline had a simultaneous and significant effect on Employee Performance at the Gajahmungkur District Office which was obtained with a calculation of 14.572 > 2.75, while the significance value is 0.001 < 0.05. Keywords: Leadership, Motivation, Work Discipline and Employee Performance